Ubiquitous Intelligence and Computing 8th International Conference, UIC 2011, Banff, Canada, September 2-4, 2011. Proceedings - UIC 2011 Banff, Alta.) (2011; Hsu, Ching-Hsien.; SpringerLink (Online service). (New York Springer, 2011)
This book constitutes the refereed proceedings of the 8th International Conference on Ubiquitous Intelligence and Computing, UIC 2010, held in Banff, Canada, September 2011. The 44 papers presented together with two keynote speeches were carefully reviewed and selected from numerous submissions. The papers address all current issues in smart systems and services, smart objects and environments, cloud and services computing, security, privacy and trustworthy, P2P, WSN and ad hoc networks, and ubiquitous intelligent algorithms and applications.
Electronic reproduction.
Keywords: Ubiquitous computing -- Congresses; Electronic books